REINTERPRETATION OF THE INGKUNG TRADITION: AN ANALYSIS OF MEANING AND CONTEXT IN JAVANESE SOCIETY BORN IN SUMATRA - Harianto II; Sutikno Sutikno; Rahmat Kartolo; Asnawi Asnawi; Herman Herman (Indonesian EFL Journal, 2026)
This study examines the reinterpretation of the Ingkung offering tradition among Javanese people born in Sumatra, particularly in Karang Anyar Village, Simalungun Regency. The study aims to answer three research questions: (1) What are the symbolic meanings of Ingkung offerings as interpreted by the community? (2) How do these offerings function as a medium of communication with God and ancestors, a symbol of harmony, and a carrier of moral values? (3) How has the Ingkung tradition been adapted in the diaspora context? This research employs a descriptive qualitative approach using Charles Sanders Peirce’s semiotic framework. Data were collected through participatory and non-participatory observations conducted over three months and in-depth interviews with 12 participants, including community leaders, traditional leaders, and local residents. Document analysis was also used to support the findings. The results reveal that Ingkung offerings function as a complex symbolic system. The Ingkung chicken, shaped in a prostrating position, symbolizes submission and devotion to God; tumpeng rice represents the cosmic mountain and harmony; while fruits signify fertility and prosperity. These elements collectively convey life messages related to gratitude, balance, and social solidarity. The study also finds that the tradition has undergone adaptation in the Sumatran context while maintaining its core philosophical values. This study contributes to the understanding of cultural reinterpretation in diaspora communities and demonstrates the applicability of Peirce’s semiotic framework in analyzing traditional rituals in contemporary socio-cultural settings.